PERBANDINGAN KONSENTRASI TRIIODOTIRONIN (T3) PADA SERUM SAPI POTONG YANG BERFOLIKEL OVARIUM KECIL DAN BESAR - , TRI UTAMI; , Dr. drh. Rr. Amelia Hana, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Triiodothyronine (T3) hormones are knows as growth hormone, organ maturation and cell metabolism, but it functions in ovarian follicles development is not well known. The purpose of this research is to know the effect of concentration serum T3 hormone in small and large ovarian follicle cows. The 14 cows samples were get from RPH Giwangan with ovarian examination by rectal before. Blood as much as 5-7 ml was collected from each cow via coccygeal vein with 10 ml spuit. Then, the samples were placed in slant position for ± 4 hours and the serum was collected. The serum brought to the Laboratory in a cooling box and was analyzed with ELISA technique. The result of the concentration serum T3 hormone from small ovarian follicle cows are 1.42 ± 0.30 μg/dL and from large ovarian follicle cows are 2.08 ± 0.37 μg/dL. As a result, the concentrations of T3 hormone in serum of large ovarian follicle cows are higher than in small ovarian follicle cows.